CHARACTERISTIC OF WUS WHO PERFOR CHARACTERISTIC OF WUS WHO PERFORM PAP SMEAR EXAMINATION AT RA KARTINI JEPARA HOSPITAL: PAP SMEAR - Resty Prima Kartika; Suci Adelia Fransisca (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Background : In Indonesia, every year more than 15,000 cases of cervical cancer are detected, and about 8,000 cases of them die. The incidence of cervical cancer in Indonesia in 2011 reached 100 per 100,000 population per year. This figure is predicted to continue to increase by 25% in the next 10 years if no prevention is not immediately taken. The purpose of the study is to find out the factors that affect wus in pap smear examination with early detection of cervical cancer at Kartini Jepara Hospital.Research Methods : This type of research uses descriptive methods, with a population of 54 with the Total sampling Technique and processed with frequency distribution. The results : of this study showed the majority of women who did pap smear examinations at RA Kartini Hospital jepara the majority of nonproductive age of 31 (57.4%) Basic education category of 37 (68.5%) Category does not work by 33 (61.1%) Multipara parity category of 41 (75.9%).Conclusions and suggestion : Based on the results of reseach that has been done, the concslusions taken from this study are characteristics of wus that perform pap smear examinations at RA Kartini Jepara Hospital dominated by nonreproductiv age wus can know and pay more attetion ti the dangers or characteristics of cervical cancer, if wus experiens this then immadiately treartmen is done to prevens the occurence of cervical cancer. Keywords : pap smear examination on wus Bibliography : 15 (2010-2018)